A Systematic Review of Proactive Work Behavior: Future Research Recommendation - Pratama, Andika Setia; Sridadi, Ahmad Rizki; Eliyana, Anis; Anggraini, Rachmawati Dewi; Kamil, Nurul Liyana Mohd (The Journal of Behavioral Science, 2023)
Fifteen years since it was first put forward, proactive work behavior has become the attention of academics within the scope of organizational behavior. The development of proactive work behavior can be observed from the increasing number of studies every year. In response to these developments, five literature reviews were conducted to provide direction for the development of proactive work behavior research. However, only one literature review has mapped out previous research on proactive work behavior. Therefore, this systematic literature review (SLR) aimed to do a broader mapping by including research samples, measurement instruments, antecedents, and consequences of proactive work behavior. A total of 70 research articles published in the Scopus database during 2007-2022 were used for this SLR. The mapping results show the dominance of employees as a research sample which covers more than half of the research articles. Meanwhile, instruments with fewer items tend to be adopted to measure proactive work behavior. The findings related to antecedents and consequences are dominated by individual aspects and do not explore team/group and organizational aspects. In response to these findings, further research needs to be directed to explore proactive work behavior in certain professional and organizational contexts. Furthermore, the measurement instrument for proactive work behavior needs to be further developed by considering organizational characteristics, both private and public sector. Regarding antecedents and consequences, team/group and organizational dynamics need to be explored further by future research so that there is no stagnation in the progress of the development of proactive work behavior studies.